FOUR SUCCESSIVE GENERATIONS OF STUDENTS AND A GRAMMAR TEST: SHOULD WE BE ALARMED? - Marjanović, Tatjana (PALIMPSEST / ПАЛИМПСЕСТ, 2018)
This paper is an attempt at developing an understanding of what seem to be rather alarming tendencies in teaching English grammar at university level. The aim was to analyze a selection of grammar tests taken by four successive generations of first-year students majoring in English at the University of Banja Luka, Bosnia and Herzegovina. In order to maintain a reasonable degree of consistency, the tests were all taken immediately after the end of a course in English grammar taught in the academic years 2011-2014, and were compared according to the following criteria: individual test scores, the ratio between passes and fails, and the highest scores achieved. The results are supposed to either dispel or confirm growing fears and suspicions that it is always this year’s English majors that perform more poorly in English grammar than their counterparts did the year before.